Valorization of viticulture waste as verjuice powders: their characterization, storage stability and application in beverage formulation - Bayram, Yuksel; Ozkan, Kubra; Sagdic, Osman (SPRINGER, 2023)
Unripe grapes are released as a waste product during viticulture. In this study, verjuices extracted from unripe grapes were encapsulated with maltodextrin (MD) and pectin (PEC) to convert into powder. The powders were evaluated for their physicochemical, phenolic properties, antioxidant capacity, encapsulation efficiency, and storage stability. The results showed that the percentage of encapsulation efficiency was significantly affected by the amounts of MD and PEC (p < 0.05), with the encapsulation efficiency ranging from 67.58 to 75.37%. The highest amount of fumaric acid was detected in verjuice and the powder, followed by caffeic acid, gallate, catechin, and epicatechin. It was found that most of these compounds were retained in the powders. Verjuice powder with pectin had significantly higher phenolic retention than powder with MD, implying that polyphenols were better retained after spray drying. With this subject studied for the first time, it can be predicted that the waste from viticulture will be transformed into powders with high-added value and find potential applications and contribute to sustainable agriculture.
Keywords: Verjuice; Microencapsulation; LC-MS/MS; FTIR; Waste; Storage stability; CARRIER; GUM; Food Science & Technology